The Evolution of a Logo Design. A Case Study of the Logo of the Presbyterian University College (Journal of Science and Technology, 2016)
Very often, people do no appreciate the thought process that goes into the production of artwork, be they logo designs or paintings and tend to under-value them. Others. including men Academics and the enlightened in society, go to the extent of believing that aerial and designers do not have any serious thought behind the artworks they produce. Some even go to the extent of saying that artist' are not intelligent people. This paper is an attempt to educate such people, to an agent, by discussing what went into the design and adoption of the new logo of the Presbyterian University college. Much research was carried out and creativity employed in the basic creative proem. from the time the request for a new logo was made to the time the design was finished. The studs it also aimed at encouraging users of the logo to appreciate the design better and help, through its application, secure and maintain the identify of the Presbyterian University College.